PENINJAUAN EFEK PENGEKANGAN DINDING PADA HUBUNGAN KOLOM , BALOK DAN DINDING AKIBAT BEBAN BERULANG LATERAL SERTA IMPLEMENTASINYA PADA PEMBANGUNAN RUMAH TAHAN GEMPA DI KABUPATEN ACEH BESAR - Cut Yusnar (Portal: Jurnal Teknik Sipil, 2011)
The function of wall which arranged from brick even from concrete in function as partition could increase strength and durability of frame structure, but actually the contribution of wall in increasing strength and ductility is often ignored. It is happened because of lack of acknowledge of behavior of frame and wall caused of axial loading that consist of cyclic lateral loading as the effect of wind load and earthquake.. In this case study it was aimed to observe the effect of wall confinement at column, beam and wall joint caused of lateral cyclic loading and it implementation on earthquake resistant housing building in Aceh Besar sub district. The strength and ductility increasing on the frame with wall and without wall (Husna, 2008) proofed that there were contribution of the increasing of strength and ductility of frame. Drift ratio of frame with wall without bed joint was 0.74. % and drift ratio of frame with wall and bed joint was 0.84 %.. In the other hand drift ratio of portal without wall was 44.85 %.Key words : strength, ductility, frame, full wall, partial wall, axial cyclic loading